1999
DOI: 10.1103/physrevb.59.4091
|View full text |Cite
|
Sign up to set email alerts
|

Defect and transmission properties of two-dimensional quasiperiodic photonic band-gap systems

Abstract: It has recently been demonstrated that two-dimensional photonic band gaps can be realized in systems comprising of a quasiperiodic arrangement of dielectric cylinders. We show that waveguides crafted out of such photonic ''quasicrystals'' can be used to guide light around sharp corners, just as in the case of periodic photonic band-gap systems, but the quasiperiodic systems tend to be more frequency selective. Because of the absence of translational symmetry, these quasiperiodic photonic band-gap structures al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 27 publications
0
49
0
Order By: Relevance
“…In preliminary numerical experiments it was verified that for an unperturbed QPC the exact position of the line source within the QPC has no influence on the unambiguous determination of the region with small LDOS in the particular structure. Only the appearance of defect modes in the LDOS of QPCs due to local configurations with two or more closely spaced cylinders depends on the chosen position of the line source [14]. These defect modes appear as sharp spectral peaks in the LDOS.…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…In preliminary numerical experiments it was verified that for an unperturbed QPC the exact position of the line source within the QPC has no influence on the unambiguous determination of the region with small LDOS in the particular structure. Only the appearance of defect modes in the LDOS of QPCs due to local configurations with two or more closely spaced cylinders depends on the chosen position of the line source [14]. These defect modes appear as sharp spectral peaks in the LDOS.…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…However, several references have reported PBGs in quasiperiodic structures. [5][6][7][8] It was also suggested that a perfect long range periodic order may not be necessary to create a spectral gap in a dielectric PBG system provided that strong Mie-resonance scattering takes place at scattering centers. In the network system, we found that the existence of photonic band gap is quite insensitive to both the periodicity and dimensionality of the lattice, but is strongly correlated with the Mie-like scattering inside a single loop of waveguides.…”
Section: Pbgs In Quasiperiodic Networkmentioning
confidence: 99%
“…4 Besides periodic structures, PBG has also been found in certain quasiperiodic systems in two dimensions. [5][6][7][8] Recently, a different kind of band gap structure for EM wave systems has been proposed. These are systems of networks made of one-dimensional waveguides, 9 which are experimentally realizable, even in an undergraduate laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al [18] reported a broad omnidirectional reflection band by combining two Fibonacci quasi-periodic structures and one periodic structure to form a heterostructures. Cheng et al [19] calculated the density of state in a photonic quasicrystal instead of the periodic crystal, and found that there the photonic band gap existed as well.…”
Section: Introductionmentioning
confidence: 99%